2004
DOI: 10.1111/j.1600-0047.2004.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, neighbourhood, and crime

Abstract: In spite of enormous changes in social conditions, psychiatric knowledge and organization of treatment, and political ambitions, schizophrenic patients still aggregate in socially deprived areas. This segregation may result in worsening of the illness as well as increasing the social disorganization in the local domicile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
2
27
0
1
Order By: Relevance
“…Caregiver burden has been described as having two components: ''objective burden'' which relates to the tangible impact of caregiving on a caregiver's life (e.g., financial loss and time lost from daily activities) and ''subjective burden'' which refers to the caregiver's perception of burden of care [6]. Caregiving burden also includes environmental burden and is associated with stigmatization and social isolation by neighbors or other acquaintances [7]. McDonnell et al [8] reported that caregiver's awareness of patient's suicidal ideation and long-term cost implications for care contribute to the burden and were significant predictors of the burden of care.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burden has been described as having two components: ''objective burden'' which relates to the tangible impact of caregiving on a caregiver's life (e.g., financial loss and time lost from daily activities) and ''subjective burden'' which refers to the caregiver's perception of burden of care [6]. Caregiving burden also includes environmental burden and is associated with stigmatization and social isolation by neighbors or other acquaintances [7]. McDonnell et al [8] reported that caregiver's awareness of patient's suicidal ideation and long-term cost implications for care contribute to the burden and were significant predictors of the burden of care.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1950s, de-institutionalization led to the closure or downsizing of asylums and formerly long-term hospitalized patients were discharged. Thus, people with chronic illnesses nowadays live in the community, although often in deprived and socially disadvantaged areas -as the paper by Lo¨gdberg et al in this issues demonstrates for schizophrenia patients in Malmo¨ (2).…”
Section: Institutionalization Revisited -With and Without Wallsmentioning
confidence: 93%
“…Accordingly, additional explanatory factors have been found to moderate this relationship including: substance misuse [12, 21]; personality disorder, specifically the presence of borderline (BPD) and antisocial personality disorder (ASPD) [22]; ethnicity, as racial inequalities are well documented within the health system in Britain [23, 24], and as such, ethnicity is an important (and politically contentious) variable that is often included but rarely explored within research studies [25]; and social vulnerabilities (e.g., victimisation and homelessness), as these factors increase ones risk for physical violence [2628], particularly in those with psychotic disorders [29]. …”
Section: Introductionmentioning
confidence: 99%